(NkOSMI^ESKOE WE]ESTWO I zEMLQ (B/s - (NdOLGOW(B, (N`RIJ aLEKSANDROWI^s ((NnOWOSIBIRSK (B:s (NnAUKA(B. (NsIB(B. (NOTD(B-(NNIE(B,s, 1986)
(NbIBLIOGR(B. (NW KONCE ST(B.s
(NbIBLIOGR(B. (NW KONCE ST(B.s
(Nan sssr SIBIRSKOE OTDELENIE IN(B-(NT GEOLOGII I GEOFIZIKIs
Keywords: (NmETEORIT tUNGUSSKIJs